2022
DOI: 10.3390/antiox11040614
|View full text |Cite
|
Sign up to set email alerts
|

SOD1 in ALS: Taking Stock in Pathogenic Mechanisms and the Role of Glial and Muscle Cells

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disorder characterized by the loss of motor neurons in the brain and spinal cord. While the exact causes of ALS are still unclear, the discovery that familial cases of ALS are related to mutations in the Cu/Zn superoxide dismutase (SOD1), a key antioxidant enzyme protecting cells from the deleterious effects of superoxide radicals, suggested that alterations in SOD1 functionality and/or aberrant SOD1 aggregation strongly contribute to ALS pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 210 publications
(280 reference statements)
0
27
0
Order By: Relevance
“…This enzyme is essential to dismutating superoxide anion into H 2 O 2 and oxygen, and it is located in the cytosol and the intermembrane mitochondrial space [ 40 , 41 ]. Mutations in the gene coding for Sod1 are linked to amyotrophic lateral sclerosis (ALS), probably through the effect of mutations on the cellular proteostatic balance [ 42 , 43 ]. The concentration of Sod1 in S. pombe, based on quantitative analysis of the fission yeast proteome, is very high under basal conditions, in the order of 4–5 µM [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…This enzyme is essential to dismutating superoxide anion into H 2 O 2 and oxygen, and it is located in the cytosol and the intermembrane mitochondrial space [ 40 , 41 ]. Mutations in the gene coding for Sod1 are linked to amyotrophic lateral sclerosis (ALS), probably through the effect of mutations on the cellular proteostatic balance [ 42 , 43 ]. The concentration of Sod1 in S. pombe, based on quantitative analysis of the fission yeast proteome, is very high under basal conditions, in the order of 4–5 µM [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The author showed that in both sporadic and familial ALS, mutations in autophagy gene were found. SOD1 was the first gene whose mutations were linked to ALS account accounting for about 3% of total ALS cases with more than 180 mutations discovered thus far linked to ALS ( Peggion et al, 2022 ).…”
Section: The Enigmatic Connection Between Circrnas Autophagy and Neur...mentioning
confidence: 99%
“…The author showed that in both sporadic and familial ALS, mutations in autophagy gene were found. SOD1 was the first gene whose mutations were linked to ALS account accounting for about 3% of total ALS cases with more than 180 mutations discovered thus far linked to ALS (Peggion et al, 2022). The accumulation of neurotoxic misfolded proteins, inclusions, and aggregates within motor neurons is the primary clinical signature in all cases of ALS.…”
Section: Interplay Between Circrnas Autophagy and Alsmentioning
confidence: 99%
“…The earliest discovered genetic predisposition in ALS was found in Cu/Zn superoxide dismutase 1 (SOD1). Mutations in SOD1 make up approximately 20% of all fALS cases and are identified in 2–7% of sALS cases [ 10 ]. In 1994, Gurney et al [ 11 ] created the first transgenic mouse model for ALS, the tg(SOD1*G93A)1Gur mice that develop ALS-like symptoms, by introducing a high copy number of the human mutated SOD1 gene (SOD1*G93A) into the mice’s genome.…”
Section: Introductionmentioning
confidence: 99%